Stability and Regime Change: The Evolution of Accounting Standards - Chen, Hui; Yang, Li (The Accounting Review, 2023)
ABSTRACT We examine the evolution of accounting regulation by linking disclosure policies and investments in a dynamic voting model. The disclosure policies are the outcome of voting by entrepreneurs, whose preferences are influenced by their investments. The investments are in turn endogenously determined by current and future disclosure policies. Absent external influences, accounting regimes are stable. A disclosure regime of high (low) quality and a strong (weak) economy coexist and reinforce each other. However, regulatory interventions can result in regime changes by changing the entrepreneurs’ expectations, even without direct enforcement. Unexpected shocks could also result in regime changes by impacting economic conditions and hence voter composition. Our analysis provides a framework to study the interaction between accounting regulation and firms’ economic decisions.